PENERAPAN INTEGRATED MARKETING COMMUNICATION (IMC) DI MEDIA RADIO SEGARA FM BANGKALAN - Ipin Rahmadi; Dewi Quraisyin (Jurusan Ilmu Komunikasi UTM, 2015)
This study intends to reveal the facts of the application of the concept of IMCwas done by radio Segara Bangkalan.Study used the concept theory of IMCwas applied of direct marketing, sales promotion, public relations, personalselling, advertising, and media interaction, marketing which relativelyapplied to the public audience of Segara radio.This of study used a qualitative descriptive method which intends to findout the phenomenon of concerns about the research subject. In holistic anddescriptive manner in the form of words and language, the data collectionmethods in this used study documentation, techniques, observation anddirectly interviews to the field.The application of IMC was good to increase the number of radio audience inSegara, from the six concepts of IMC, advertising, public relations, personalselling, sales promotion, direct marketing, and interactive ware marketing,applied directly by radio to the public, so that produce good results againstthe Segara radio.Keywords: IMC (Integrated Marketing Communication), Media Radio,Audience